Tongues Will Cease: An Evaluation of Cessationism Based on 1 Corinthians 13:8-12 - Suwanto, Wilson W. (Universitas Syiah Kuala, 2023)
The general view is that speaking in tongues will cease at Jesus' second coming as is the understanding of 1 Corinthians 13:8-12. This passage of Scripture is often used to disprove the fallacy of the Cessationist view that the gift of tongues has ceased since the Bible was written. The emphasis falls on the phrase